DUDUK SAMA RENDAH, BERDIRI SAMA TINGGI Nilai-Nilai Budaya Nelayan & Petambak di Sambas, Kalimantan Barat - Pridaningsih, Deliana R. (Sabda: Jurnal Kajian Kebudayaan, 2008)
Until now, the traditional fishermen and fish farmers of Sambas still uphold traditional values as implemented as hereditary greet, such as drink coffee together and Saprahan meal which are small things for people of other communities. For these fishermen and fish farmers these daily activities mean a lot to tighten the brotherhood. In the midst of their life pressure, they kept alive these simple cultural values.